Analysis of student learning attitudes in cad system pattern making learning at SMKN 1 Wonosari - Safitri, Nadya Kamilia; Sugiyem, Sugiyem; Arviana, Shyevita Ines (Faculty of Engineering, Universitas Negeri Yogyakarta, 2023)
A learning attitude is a person's willingness and readiness to learn and develop in the learning process. Learning attitude is essential in the learning process, because a positive learning attitude will help students to more easily understand and master the material on study, be more enthusiastic and motivated to learn, and be more able to apply what they have learned in everyday life. This study aims to determine student learning attitudes in learning CAD system pattern-making in class XII at SMKN 1 Wonosari. This research is quantitative and descriptive. The population in this study was 66 students of class XII. The research sample was determined randomly using Harry King's Nomogram calculation formula with 43 students. The data collection instrument used was a questionnaire. Test the tool's validity using the Pearson product-moment and reliability test using the Cronbach alpha formula—data analysis techniques using descriptive statistics. The results showed that the learning attitude of students in class XII Fashion Design at SMKN 1 Wonosari in learning the CAD system skirt pattern was good. Based on the results of data analysis where 2% are in the